INFLUENCE OF LEADERSHIP STYLE, COMPENSATION AND WORK CLIMATE ON WORK MOTIVATION - Saputra, Nika; Mulia, Rizki Afri (Efisiensi : Kajian Ilmu Administrasi, 2021)
Abstract: The Influence of Leadership Style, Compensation and Work Climate on Work Motivation of Vocational School Teachers.                                                                                                           This research aimed to determine the effect of leadership style, Compensation, and work climate on teachers' work motivation of SMK Batang Anai District, Padang Pariaman Regency. This type of research is quantitative approach research. The population in this study amounted to 83 vocational school teachers in Batang Anai District, Padang Pariaman Regency. The sample in this study was 41 people after being searched by the systematic sampling technique. They are collecting data in this study using a direct closed questionnaire method. The results of the path analysis test show that (1) there is an influence of leadership style on the work motivation of Vocational High School teachers in Batang Anai District, Padang Pariaman Regency (2) there is an effect of Compensation on the work motivation of Vocational High School teachers in Batang Anai District, Padang Pariaman Regency (3) there is an influence of the work climate on the work motivation of Vocational High School teachers in Batang Anai District, Padang Pariaman Regency.  Keyword: Leadership Style; Compensation; Work Climate; Work Motivation Abstrak: Pengaruh Gaya Kepemimpinan, Kompensasi, dan Iklim Kerja Terhadap Motivasi Kerja Guru SMK.                                                                                                                                                     Tujuan penelitian ini adalah untuk mengetahui pengaruh Gaya Kepemimpinan, Kompensasi, dan Iklim Kerja terhadap Motivasi Kerja Guru SMK Kecamatan Batang Anai Kabupaten Padang Pariaman. Jenis penelitian yang digunakan adalah penelitian dengan pendekatan kuantitatif. Populasi dalam penelitian ini berjumlah 83 guru SMK di Kecamatan Batang Anai Kabupaten Padang Pariaman. Sampel dalam penelitian ini sebanyak 41 orang setelah dilakukan pencarian dengan teknik sampling sistematis. Pengumpulan data dalam penelitian ini dilakukan dengan metode angket tertutup langsung. Hasil uji analisis jalur menunjukkan bahwa (1) terdapat pengaruh gaya kepemimpinan terhadap motivasi kerja guru SMK di Kecamatan Batang Anai Kabupaten Padang Pariaman (2) terdapat pengaruh Kompensasi terhadap Motivasi Kerja Guru. Guru SMK di Kecamatan Batang Anai Kabupaten Padang Pariaman (3) terdapat pengaruh iklim kerja terhadap motivasi kerja guru SMK di Kecamatan Batang Anai Kabupaten Padang Pariaman.  Kata Kunci: Gaya Kepemimpinan; Kompensasi; Iklim Kerja; Motivasi Kerja